Identification of a potential marker for Brugia malayi infection by Western Blot analysis - N., Rahmah; A., Noor A'shikin; R., Mehdi; B., Abdullah; A., Khairul Anuar
Brugia malayi adult antigen was electrophoresed on SDS-PAGE gels and electrophoretically transferred onto PVDF membranes. The membrane strips were incubated with different categories of human sera, followed by successive incubations with blocking solution, monoclonal anti-human IgG4 antibody and peroxidase rabbit anti-mouse IgG antibody; with adequate washings done in between each incubation steps. Chemiluminescence detection was used to develop the blots. Two antigenic epitopes (molecular weights of -67-68 kDa and -54-55 kDA) were found to be present in the Western blots of all microfilaraemic sera, all amicrofilaraemic sera with positive anti-filarial IgG4 antibodies, some treated patients and some elephantiasis patients. We hypothesized that last two groups are still harbouring live adult worms despite being treated or in the chronic stage respectively. The two epitopes did not simultaneously react with soil-transmitted helminth sera, normal endemic sera and sera of city dwellers.Therefore the simultaneous presence of both epitopes may potentially serve as a marker for Brugia malayi infection.